The Autonomy of Pesantren in The One Pesantren One Product (OPOP) Program: Mentoring, Training or Grant Funding Driven? - Nurhasanah, Elis; Zahra, Qiny Shonia Az; Mubarok, Acep Zoni Saeful; Rahmat, Biki Zulfikri (Universitas Siliwangi, 2024)
Introduction to The Problem: One pesantren one product is a program of the governor of West Java province which aims to make pesantren self-reliant, among its programs is to provide assistance, training and grant funds to pesantren that have businesses both start-up and scale up.Purpose/Objective Study: the purpose of this study was to analyze the effect of assistance, training and grant funds on pesantren independence.Design/Methodology/Approach: The population in this study was 285 pesantren in Tasiknalaya City and Regency. The sample in this study was 48 respondents, using online and offline questionnaires as the distribution media. The research sample was taken using a purposive random sampling approach with the following criteria; (1) are OPOP participants in 2019-2023, (2) are in the Tasikmalaya City/RegencyFindings: the results show that The mentoring, training and grants provided by the governor's of West Java province affect the independence of pesantren in the city and district of Tasikmalaya, with a large influence of 69%.Paper Type: Research Article